Pengaruh Earnings Quality terhadap Firm Value dengan Financial Performance sebagai variabel intervening pada perusahaan yang terdaftar pada perusahaan LQ 45 - Anneke Kusuma Dewi; Devie Devie Devie (Business Accounting Review, 2017)
This study aimed to examine the influence of earnings quality to firm value through financial performance as an intervening variable. Earnings quality measured by using smoothness, firm value measured by using Tobin’s Q and financial performance measured by using ROA. This study was conducted on miscellaneous industry firms in Indonesia in the period of 2013 to 2015 with a total sample of 44 firm years.The results of this research indicated a positive influence of earnings quality to financial performance. Earnings quality had a positive influence to firm value. Financial performance had a positive influence to firm value.